Case Report: Improvement of Visual Function of a Cerebral Palsied Child with Periodic Exotropia of the Divergence Excess Type - Robertson, K M (Canadian Journal of Optometry, 1984)
Frequently, children who have a systemic disease which coincides with a very high incidence of visual anomalies are considered untreatable. This article describes the visual therapy given to a 10 year old child with cerebral palsy and the apparent success of the treatment.